Sodium trimetaphosphate combined to calcium as a strategy to improve dentin-bonding interface - Gonçalves, Rafael Simões; Speranza Zabeu, Giovanna; Saori Hissano, Wendy; Ciccone Giacomini, Marina; Mendes Cândia Scaffa, Poliana; Rios, Daniela; Marques Honório, Heitor; Wang, Linda (Brazilian Dental Science, 2022)
Objective: The aim of this study was to evaluate the effect of STMP as biomimetic analog of dentin matrix onthe dentin bond strength submitted to artificial cariogenic challenge over time. Material and Methods: The totalnumber of teeth used in the experiment was 60 teeth, which were divided into 6 groups (n = 10). Of these totalamount, 10 teeth were not submitted to the artificial cariogenic challenge (ACC), serving as control group (SoundDentin - SD) while the other 50 were submitted to an ACC (7d/37ºC), being treated with treatment solutionsaccording to each group: SD- deionized water/sound dentin, CD- deionized water/ artificial caries dentin, GIIISTMP,GIV- STMP + Ca(OH)2, GV- STMP + NaF, and GVI- NaF. After treatments (24h), the specimens wererestored (Adper Single Bond Universal + Filtek Z250), to obtain resin–dentin sticks with a cross sectional area of0.8mm2, approximately. Two-third of these sticks were stored in artificial saliva (37°C) for analyzes after 6 and12 months. The 1/3 remains were subjected to mTBS test (baseline). Data were analyzed by two-way ANOVAand Tukey tests (p